Evidence for Broad Versus Segregated Projections from Cholinergic and Noradrenergic Nuclei to Functionally and Anatomically Discrete Subregions of Prefrontal Cortex - Chandler, Daniel J.; Waterhouse, Barry D. (Frontiers in Behavioral Neuroscience, 2012)
The prefrontal cortex (PFC) is implicated in a variety of cognitive and executive operations. However, this region is not a single functional unit; rather, it is composed of several functionally and anatomically distinct networks, including anterior cingulate cortex (ACC), medial prefrontal cortex (mPFC) and orbitofrontal cortex (OFC). These prefrontal subregions serve dissociable behavioral functions, and are unique in their afferent and efferent connections. Each of these subregions is innervated by ascending cholinergic and noradrenergic systems, each of which likewise has a distinct role in cognitive function; yet the distribution and projection patterns of cells in the source nuclei for these pathways have not been examined in great detail. In this study, fluorescent retrograde tracers were injected into ACC, mPFC and OFC, and labeled cells were identified in the cholinergic nucleus basalis of Meynert (NBM) and noradrenergic nucleus locus coeruleus (LC). Injections into all three cortical regions consistently labeled cells primarily ipsilateral to the injection site with a minimal contralateral component. In NBM, retrogradely labeled neurons were scattered throughout the rostral half of the nucleus, whereas those in LC tended to cluster in the core of the nucleus, and were rarely localized within the rostral or caudal poles. In NBM, more than half of all retrogradely labeled cells possessed axon collaterals projecting two or more PFC subregions. In LC, however, only 4.3% of retrogradely labeled neurons possessed collaterals targeting any two prefrontal subregions simultaneously, and no cells were identified that projected to all three regions. Of all labeled LC neurons, 49.3% projected only to mPFC, 28.5% projected only to OFC, and 18.0% projected only to ACC. These findings suggest that subsets of LC neurons may be capable of modulating neuronal activity in individual prefrontal subregions independently, whereas assemblies of NBM cells may exert a more unifi